Rapid Repeat Birth: Intersections Between Meaning-Making and Situational Support Among Multiparous Adolescent Mothers. - Reddy, Julia.; Mistry, Jayanthi.; Jacobs, Francine Helene. (Tufts University. Tisch Library., 2017)
This study examined interpretations of motherhood among adolescents who have experienced rapid repeat births (second births within 24 months of the primiparous birth) Analyses of participants' descriptions of their transitions to motherhood indicate four modal narratives that vary along two axes: the adoption of a motherhood identity, and the nature (or stability) of relational support available. By using subjective perceptions of motivation, stability, and feelings of competence, this study linked intrapersonal meaning-making with situational sources of support to describe various pathways through repeat adolescent childbearing in a way that both confirms and enriches extant literature. The implications of this study instruct home visiting programs and other interventions designed to forestall repeat pregnancies by elucidating pathways of reinforcement or increased risk inherent in some maternal trajectories. Following this logic, interventions directed at improving outcomes for young mothers and their children would do well to consider the interplay between internal meaning-making, relational support, and the transformative power of adopting the mother identity.